A survey of national and multi-national registries and cohort studies in juvenile idiopathic arthritis: challenges and opportunities - Timothy Beukelman; Janneke Anink; Lillemor Berntson; Ciaran Duffy; Justine A. Ellis; Mia Glerup; Jaime Guzman; Gerd Horneff; Lianne Kearsley-Fleet; Ariane Klein; Jens Klotsche; Bo Magnusson; et al. (BMC, 2017)
Abstract Background To characterize the existing national and multi-national registries and cohort studies in juvenile idiopathic arthritis (JIA) and identify differences as well as areas of potential future collaboration. Methods We surveyed investigators from North America, Europe, and Australia about existing JIA cohort studies and registries. We excluded cross-sectional studies. We captured information about study design, duration, location, inclusion criteria, data elements and collection methods. Results We received survey results from 18 studies, including 11 national and 7 multi-national studies representing 37 countries in total. Study designs included inception cohorts, prevalent disease cohorts, and new treatment cohorts (several of which contribute to pharmacosurveillance activities). Despite numerous differences, the data elements collected across the studies was quite similar, with most studies collecting at least 5 of the 6 American College of Rheumatology core set variables and the data needed to calculate the 3-variable clinical juvenile disease activity score. Most studies were collecting medication initiation and discontinuation dates and were attempting to capture serious adverse events. Conclusion There is a wide-range of large, ongoing JIA registries and cohort studies around the world. Our survey results indicate significant potential for future collaborative work using data from different studies and both combined and comparative analyses.